Avaliação da limpeza da superfície dentinária de canais radiculares de molares após utilização de diferentes sistemas de irrigação - Erika Sales Joviano Pereira (2009)
The aim of the study was to assess, through stereomicroscope (SM) and scanning electron microscopy (SEM), the walls cleanliness of the molars root canals on the apical one-third with three different irrigation systems: Needle Irrigation, Endo Activator System and EndoVac System. Canal preparations were made in forty five mandibular human molars with ProTaper Universal System. The teeth were divided into three groups: G1: needle irrigation group 15 teeth irrigated with NaOCl 5.25% and final flush with EDTA 17% using a 27X4 gauge needle; G2: sonic irrigation group 15 teeth irrigated with NaOCl 5.25% using a 27X4 gauge needle and sonic activation (Endo Activator) during 60s of each solution NaOCl and EDTA, after conventional cleaning and shaping; G3: vacuum irrigation group 15 teeth irrigated with the Endo Vac with macrocannula and micro irrigation cycles after the preparation phase with the same reagents NaOCl and EDTA. Subsequently, the roots were sectioned and observed under SM and SEM. The images had their apical third analyzed by three independent examiners in a semi-quantitative manner in accordance with the following scores: (1) small debris quantity; (2) moderate debris quantity and (3) dense debris quantity. The results demonstrated trough the ANOVA test that in relation to the anatomical factors angle and curvature radius there wasn'st significant difference on their mean values between groups and they haven't influence on the capacity of debris removal. Comparison between groups trough Kruskal-Wallis test revealed that at the apical one third the teeth halves from Groups 1 and 2 did not differ significantly (p > 0.05) and their capacity of debris removal was 70% and 64% respectively; both had significantly less surface debris (p < 0.05) than the Group 3 which presented capacity of debris removal of 44%. The conventional and sonic irrigation methods were similar in the capacity of debris removal and performed significantly better than did the vacuum irrigation.